Paper-based sample-to-answer molecular diagnostic platform for point-of-care diagnostics - Choi, J.R.; Tang, R.; Wang, S.; Wan Abas, Wan Abu Bakar; Pingguan-Murphy, Belinda; Xu, F. (Elsevier, 2015)
Nucleic acid testing (NAT), as a molecular diagnostic technique, including nucleic acid extraction, amplification and detection, plays a fundamental role in medical diagnosis for timely medical treatment. However, current NAT technologies require relatively high-end instrumentation, skilled personnel, and are time-consuming. These drawbacks mean conventional NAT becomes impractical in many resource limited disease-endemic settings, leading to an urgent need to develop a fast and portable NAT diagnostic tool. Paper-based devices are typically robust, cost-effective and user-friendly, holding a great potential for NAT at the point of care. In view of the escalating demand for the low cost diagnostic devices, we highlight the beneficial use of paper as a platform for NAT, the current state of its development, and the existing challenges preventing its widespread use. We suggest a strategy involving integrating all three steps of NAT into one single paper-based sample-to-answer diagnostic device for rapid medical diagnostics in the near future. (C) 2015 Elsevier B.V. All rights reserved.